(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The teaching of speaking skills in second language acquisition has evolved from a focus on grammatical accuracy to an emphasis on meaningful communication. This shift reflects the theoretical distinction between linguistic competence and communicative competence. Linguistic competence, as defined by Noam Chomsky, refers to the mastery of the grammatical system of a language, including syntax, morphology, phonology, and semantics.